Cause or consequence? The role of IL-1 family cytokines and receptors in neuroinflammatory and neurodegenerative diseases - Boraschi, Diana; Italiani, Paola; Migliorini, Paola; Bossù, Paola (Frontiers in Immunology, 2023)
Cytokines and receptors of the IL-1 family are key mediators in innate immune and inflammatory reactions in physiological defensive conditions, but are also significantly involved in immune-mediated inflammatory diseases. Here, we will address the role of cytokines of the IL-1 superfamily and their receptors in neuroinflammatory and neurodegenerative diseases, in particular Multiple Sclerosis and Alzheimer’s Disease. Notably, several members of the IL-1 family are present in the brain as tissue-specific splice variants. Attention will be devoted to understanding whether these molecules are involved in the disease onset or are effectors of the downstream degenerative events. We will focus on the balance between the inflammatory cytokines IL-1 and IL-18 and inhibitory cytokines and receptors, in view of future therapeutic approaches.